2020
DOI: 10.1155/2020/8593617
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan Protects against Doxorubicin-Induced Cardiotoxicity by Regulating the PTEN/Akt Pathway

Abstract: Background and Aims. Myocyte apoptosis plays a critical role in the development of doxorubicin- (DOX-) induced cardiotoxicity. In addition to its cardiotonic effect, laboratory evidence indicates that levosimendan can inhibit apoptosis, but its role in DOX-induced cardiac injury remains unclear. Therefore, the present study is aimed at exploring whether levosimendan could attenuate DOX-induced cardiotoxicity. Methods. Levosimendan (1 mg/kg) was administered to mice through oral gavage once daily for 4 weeks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Levosimendan preconditioning has been shown to protect cardiomyocytes against apoptosis [ 9 13 ]. Moreover, it exerted comparable antiapoptotic effects in organs such as the liver, lungs, and kidneys [ 20 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levosimendan preconditioning has been shown to protect cardiomyocytes against apoptosis [ 9 13 ]. Moreover, it exerted comparable antiapoptotic effects in organs such as the liver, lungs, and kidneys [ 20 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…During open-heart surgery, levosimendan has been successfully used to treat preoperative and perioperative cardiac failure [ 7 , 8 ]. Levosimendan preconditioning prevented myocardial ischemic damage and inhibited cardiomyocyte apoptosis in ischemia-reperfusion (I/R) models [ 9 13 ]. Clinically, in addition to ischemia-reperfusion injury, a significantly high number of patients present with myocardial infarction (MI) due to prolonged acute coronary artery occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining the role of individual p38 isoforms, particularly the alternative isoforms p38γ and p38δ, in DOX-induced cardiotoxicity reported that p38δ plays an important role in promoting DOX-induced cardiotoxicity in females by inhibiting autophagy [37]. Conversely, many reports suggest that PI3k/Akt signaling, one of the most important kinases in the regulation of cell survival, has a significant effect on the inhibition of DOX-induced cardiotoxicity [38][39][40][41]. Indeed, the upregulation of the PI3k/Akt expression can inhibit apoptosis and improve DOX-induced cardiotoxicity [41][42][43].…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…However, co-treatment of LEV showed a significant improvement in the activity of all three complexes in a dose-dependent manner. Based on the evidence, LEV can maintain mitochondrial function by improving respiration and modulation of mitochondrial calcium homeostasis 8 30 . Therefore, the present study's findings indicate that LEV can improve the renal tissue's complex activities and cellular energy supply in AlP-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%